Method for improving energy density of lithium iron phosphate positive electrode material by composite carbon nanomaterial

CN122977342APending Publication Date: 2026-10-27ZHONGJIN CARBON ENERGY NEW MATERIAL TECHNOLOGY (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611326619.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,该方法存在明显不足:首先,热解所得的无定形碳层导电性有限,且包覆均匀性难以精确控制,容易形成局部过厚或缺失,导致部分活性材料未能有效连接入导电网络,限制了倍率性能的充分发挥;其次,单一的碳包覆层在充放电过程中,对磷酸铁锂颗粒的体积变化缓冲作用有限,长期循环下可能导致包覆层破裂与导电网络退化;再者,为获得连续包覆层而增加碳含量时,又会显著降低材料的振实密度与体积能量密度;此外,一些研究尝试直接混合碳纳米管或石墨烯,但由于其易团聚且与基体界面结合弱,难以形成均匀、稳定且贯穿整体的三维导电结构,工艺复杂性和重复性是该技术路线面临的主要挑战

Benefits of technology

相比于现有技术,本发明通过采用多壁碳纳米管与石墨烯构成的混合碳纳米材料体系,并精确控制其质量比例,构建了一个协同作用的三维导电网络。该网络中,石墨烯片层提供大面积的二维导电平面与接触界面,而碳纳米管则起到连接离散石墨烯片层及磷酸铁锂颗粒的“导电桥梁”作用,有效防止了二维材料的重新堆叠。这种点-面结合的结构在电极内部形成了更为连续和高效的电子传输路径,显著降低了电池的内部阻抗,使得活性物质的利用率得到大幅提升。能够在较低的总碳含量下实现更优的导电效果,有助于维持电极较高的振实密度,从而同步提升材料的质量能量密度与体积能量密度,同时改善了电极的倍率充电放电能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977342A_ABST
    Figure CN122977342A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium ion battery positive electrode materials, and particularly discloses a method for improving the energy density of a lithium iron phosphate positive electrode material by using a composite carbon nanomaterial. The core of the method is that: a carbon nanomaterial with a specific size and proportion, such as a mixture of carbon nanotubes and graphene, is uniformly mixed with a lithium iron phosphate precursor by a dry method or a wet method; then, heat treatment is carried out at 500 DEG C to 900 DEG C under a protective atmosphere, so that the carbon nanomaterial and the lithium iron phosphate form a stable composite structure; finally, the final product is obtained through controllable cooling and post-processing. The method significantly improves the electronic conductivity and structural stability of the material by constructing a three-dimensional efficient conductive network and strengthening the interface combination, so that the energy density of the lithium iron phosphate positive electrode material is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery cathode materials technology, and more specifically, to a method for improving the energy density of lithium iron phosphate cathode materials by using composite carbon nanomaterials. Background Technology

[0002] Lithium iron phosphate (LFP) cathode materials occupy an important position in lithium-ion power batteries and large-scale energy storage due to their high safety, long cycle life, and cost advantages. In recent years, with the increasing demands for electric vehicle range and the growing energy density requirements of energy storage systems, domestic and international research has focused on how to further improve the energy density of LFP materials. The technological development has progressed from early material nanosizing to shorten the lithium-ion diffusion path, to bulk doping to improve intrinsic conductivity, and now to the widely adopted carbon coating technology aimed at constructing conductive networks. Current technological trends are evolving towards multi-component composites and precise structural design; introducing novel carbon materials to construct more efficient three-dimensional conductive structures is a major research direction in the field.

[0003] In existing technologies, the most common method to improve the conductivity of lithium iron phosphate materials is carbon coating, typically using organic carbon sources such as glucose and sucrose to pyrolyze at high temperatures to form an amorphous carbon layer. However, this method has significant drawbacks: First, the conductivity of the amorphous carbon layer obtained by pyrolysis is limited, and the uniformity of the coating is difficult to control precisely, easily leading to local over-thickness or gaps, resulting in some active materials failing to effectively connect into the conductive network and limiting the full realization of rate performance; second, a single carbon coating layer has limited buffering effect on the volume changes of lithium iron phosphate particles during charge and discharge, and long-term cycling may lead to coating layer rupture and conductive network degradation; third, increasing the carbon content to obtain a continuous coating layer significantly reduces the tap density and volumetric energy density of the material; in addition, some studies have attempted to directly mix carbon nanotubes or graphene, but due to their tendency to aggregate and weak interfacial bonding with the matrix, it is difficult to form a uniform, stable, and integral three-dimensional conductive structure, and the complexity and repeatability of the process are the main challenges facing this technical route.

[0004] Therefore, a method to improve the energy density of lithium iron phosphate cathode materials by using composite carbon nanomaterials is proposed to address the above problems. The core issue to be solved is how to overcome the problems of low conductive network efficiency, poor structural stability and weak interfacial bonding with active materials in existing carbon coating technologies, so as to substantially improve the energy density of lithium iron phosphate cathode materials, especially their rate performance and cycle stability, without sacrificing material compaction density and process feasibility. Summary of the Invention

[0005] In order to overcome the above-mentioned defects of the prior art, embodiments of the present invention provide a method for improving the energy density of lithium iron phosphate cathode materials by using composite carbon nanomaterials, so as to solve the problems mentioned in the background art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for improving the energy density of lithium iron phosphate cathode materials by using composite carbon nanomaterials, the method comprising the following steps: S1: Provide a lithium iron phosphate cathode material precursor, wherein the precursor is prepared by mixing a lithium source compound, an iron source compound and a phosphorus source compound in a stoichiometric ratio, and wherein the average particle size of the precursor is in the range of 0.1 μm to 20 μm; S2: Provide carbon nanomaterials, said carbon nanomaterials being selected from carbon nanotubes, graphene, reduced graphene oxide, carbon nanofibers and combinations thereof, wherein the size of said carbon nanomaterials is in the range of 10 nm to 100 μm in length and 1 nm to 100 nm in diameter, and the amount of added carbon nanomaterials accounts for 0.5% to 15% of the total mass of the composite cathode material; S3: The carbon nanomaterials are uniformly mixed with the lithium iron phosphate cathode material precursor by dry mixing or wet mixing to form a mixture. The mixing intensity and time are controlled during the mixing process to ensure that the carbon nanomaterials are uniformly dispersed in the lithium iron phosphate. S4: The mixture is heat-treated under a protective atmosphere at a temperature between 500°C and 900°C for a time between 1 hour and 12 hours to form a composite structure between carbon nanomaterials and lithium iron phosphate, thereby obtaining a carbon nanomaterial composite lithium iron phosphate cathode material. S5: Cooling and optional post-processing steps are performed on the composite cathode material. The cooling adopts a controllable cooling method with a cooling rate in the range of 1℃ / min to 10℃ / min. The post-processing includes grinding and sieving to obtain the target particle size distribution.

[0007] Preferably, in S2, the carbon nanomaterial is a mixture of multi-walled carbon nanotubes and graphene, wherein the mass ratio of multi-walled carbon nanotubes to graphene is between 1:0.2 and 1:5, and in S3, the mixing is achieved by mechanical stirring or ultrasonic-assisted dispersion, and the mixing time is in the range of 1h to 10h.

[0008] Preferably, in S3, the dry mixing is carried out using a ball mill, with a milling speed between 100 r / min and 500 r / min and a milling time between 3 h and 15 h; the wet mixing is carried out using a solvent dispersion method, with the solvent including water or an organic solvent, and ultrasonic energy is applied during the dispersion process, with an ultrasonic power between 100 W and 1000 W and a dispersion time between 30 min and 5 h.

[0009] Preferably, in S4, the heat treatment step is carried out under an inert atmosphere, which includes nitrogen or argon, and the gas flow rate is controlled between 0.5 L / min and 5 L / min. The heat treatment process includes heating to the target temperature at a heating rate of 2°C / min to 10°C / min and holding at that temperature for a certain period of time, which is in the range of 2 h to 8 h.

[0010] Preferably, the method further includes preforming the mixture before S4 by forming a blank through tableting or granulation to enhance the physical contact between the carbon nanomaterials and lithium iron phosphate, with the preforming pressure in the range of 10 MPa to 100 MPa.

[0011] Preferably, in S2, the carbon nanomaterial undergoes a pretreatment step before composite processing. The pretreatment includes acid washing purification or surface functionalization modification. The acid washing is performed by refluxing concentrated nitric acid or concentrated sulfuric acid at a temperature of 60°C to 100°C for 1 to 6 hours. The surface functionalization modification is achieved by chemical grafting or plasma treatment.

[0012] Preferably, in S5, the post-processing step includes air jet milling or vibratory sieving of the composite cathode material to obtain a final product with a particle size distribution between 1 μm and 50 μm.

[0013] Preferably, the method further includes a material characterization step after S5, in which the uniformity of the composite structure is examined by X-ray diffraction or scanning electron microscopy.

[0014] Preferably, in S2, the carbon nanomaterials include functionalized carbon nanomaterials, which are functionalized by introducing oxygen- or nitrogen-containing functional groups. In S3, a stepwise mixing method is adopted, in which a portion of the carbon nanomaterials are first mixed with the lithium iron phosphate precursor, then heat treatment is performed in S4, and then the remaining carbon nanomaterials are added for secondary mixing.

[0015] Preferably, in S3, the mixing process further includes adding a dispersant to promote uniform dispersion of the carbon nanomaterials, wherein the amount of the dispersant is 0.1% to 5% of the total mass of the mixture, and the dispersant is selected from surfactants or polymeric dispersants.

[0016] The technical effects and advantages of this invention are as follows: Compared to existing technologies, this invention employs a hybrid carbon nanomaterial system composed of multi-walled carbon nanotubes and graphene, and precisely controls their mass ratio to construct a synergistic three-dimensional conductive network. In this network, graphene sheets provide large-area two-dimensional conductive planes and contact interfaces, while carbon nanotubes act as "conductive bridges" connecting discrete graphene sheets and lithium iron phosphate particles, effectively preventing the re-stacking of two-dimensional materials. This point-to-surface combined structure forms a more continuous and efficient electron transport path within the electrode, significantly reducing the battery's internal impedance and greatly improving the utilization rate of active materials. Achieving superior conductivity with a lower total carbon content helps maintain a high tap density of the electrode, thereby simultaneously improving the material's mass energy density and volumetric energy density, while also enhancing the electrode's rate charge / discharge capability.

[0017] Compared to existing technologies, this invention achieves highly uniform dispersion and tight interfacial bonding of carbon nanomaterials in a lithium iron phosphate matrix by pre-treating the carbon nanomaterials with acid washing and purification or surface functionalization before composite formation, and employing a combination of stepwise mixing and preforming processes. Acid washing removes metal catalyst impurities from the carbon nanomaterials and introduces functional groups such as carboxyl groups, while modification methods such as plasma treatment further enhance their surface activity. The subsequent stepwise mixing process—introducing a portion of the carbon nanomaterials for initial mixing and heat treatment to form a stable composite base, and then introducing the remaining portion for secondary mixing—effectively avoids the agglomeration problem caused by adding all carbon sources at once. The preforming step, by applying pressure, forms a preform from the mixture, greatly enhancing the physical contact between particles. This ensures that the final composite has a highly uniform microstructure, guarantees the integrity of the conductive network, reduces the risk of excessively high local current density, and thus improves the cycling stability and consistency of the material.

[0018] Compared to existing technologies, this invention optimizes the heat treatment process, specifically controlling the heating rate from 2°C / min to 10°C / min, and holding the temperature for 1 to 12 hours within a specific temperature range of 500°C to 900°C, followed by controlled cooling at 1°C / min to 10°C / min. This achieves the synergistic construction and stabilization of carbon nanomaterials and lithium iron phosphate crystal structures. The precisely controlled heating process facilitates the gradual decomposition of the organic precursor and the ordered graphitization of carbon, forming a conductive phase with better crystallinity. The suitable holding temperature and time ensure sufficient growth of lithium iron phosphate grains without excessive reduction, while promoting the formation of a stable interface between carbon nanomaterials and lithium iron phosphate particles through chemical bonding. The slow cooling process helps release the internal stress generated at high temperatures, stabilizing the crystal structure. This allows for the formation of a high-quality conductive network while maintaining the integrity of the lithium iron phosphate main structure, resulting in a composite cathode material that not only has high initial capacity but also excellent structural stability. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of battery test data from Embodiment 1 of the present invention.

[0020] Figure 2 This is a SEM image of the battery in Embodiment 1 of the present invention.

[0021] Figure 3 This is a flowchart illustrating the overall workflow of the method of the present invention.

[0022] Figure 4 This is a detailed diagram of the mixing process of the present invention.

[0023] Figure 5 This is a schematic diagram of the heat treatment process of the present invention. Detailed Implementation

[0024] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] As attached Figures 1 to 5 The method for improving the energy density of lithium iron phosphate cathode materials by using composite carbon nanomaterials is shown below, and its specific implementation details are as follows: Example 1: Improving the energy density of lithium iron phosphate cathode material through composite carbon nanomaterials The first step is raw material preparation: lithium carbonate, ferrous oxalate, and ammonium dihydrogen phosphate are accurately weighed as precursor raw materials and mixed according to a lithium:iron:phosphorus molar ratio of 1.05:1:1. This slight excess of lithium source is used to compensate for lithium volatilization loss during the high-temperature treatment process. The prepared raw materials are placed in a high-speed mixer and mixed for 6 hours to ensure uniform mixing at the molecular level, obtaining the lithium iron phosphate precursor. Its average particle size is measured to be 5 μm using a laser particle size analyzer, and the particle size distribution range is controlled between 2-10 μm.

[0026] A composite system of multi-walled carbon nanotubes and graphene is employed, wherein the multi-walled carbon nanotubes have a length of 10-50 μm, a diameter of 10-20 nm, and a specific surface area of ​​220 m². 2 / g; Graphene sheets have a diameter of 5-15μm, a thickness of 3-8 layers, and a specific surface area of ​​420m². 2 / g. The mass ratio of the two materials is precisely controlled at 1:2, and the total addition accounts for 5% of the total mass of the composite cathode material. Before use, the carbon nanomaterials are pretreated: multi-walled carbon nanotubes are refluxed in concentrated nitric acid at 85°C for 4 hours, then repeatedly washed with deionized water until the pH value is 6.5-7.5, and finally vacuum dried at 100°C for 12 hours. This treatment can effectively remove impurities from the metal catalyst and introduce carboxyl functional groups into the tube wall.

[0027] Pretreated lithium iron phosphate precursor and carbon nanomaterials were placed in a planetary ball mill jar in a specific ratio. Zirconia ceramic balls were used as the milling media, and the ball-to-material ratio was precisely controlled at 10:1. The milling process was carried out under argon protection, with a rotation speed set at 300 rpm for 8 hours. A 15-minute pause was taken every 2 hours to prevent overheating from affecting material properties. After milling, the mixing effect was observed using a field emission scanning electron microscope. It was observed that the carbon nanomaterials were uniformly coated on the surface of the lithium iron phosphate particles, forming a preliminary conductive network.

[0028] In the preforming stage, the uniformly mixed materials are pressed into cylindrical blanks with a diameter of 20 mm and a thickness of 3 mm under a pressure of 50 MPa.

[0029] The pressing process employs a stepped pressurization method: first, the pressure is increased to 20 MPa at a rate of 10 MPa / min and held for 2 minutes; then, the pressure is increased to 50 MPa at a rate of 5 MPa / min and held for 5 minutes. This pressurization method helps to expel air between materials and enhances the contact density between particles.

[0030] The heat treatment process was carried out in a vertical tube furnace. The billet was evenly placed in an alumina crucible, and high-purity argon was introduced as a protective atmosphere, with the gas flow rate precisely controlled at 2 L / min. The heating program consisted of three stages: from room temperature to 300°C at a rate of 5°C / min, held for 1 hour to completely remove adsorbed water; then to 700°C at a rate of 3°C / min, held at this temperature for 6 hours; and finally, cooled to room temperature at a rate of 3°C / min. The entire heat treatment process lasted approximately 20 hours, and precise temperature control ensured the formation of a stable composite structure between the carbon nanomaterials and lithium iron phosphate.

[0031] The post-processing steps include crushing, grinding, and grading. First, the heat-treated lumpy material is coarsely crushed in a jaw crusher, then finely ground using an air jet mill at a working pressure of 0.8 MPa. The ground material is then graded using an ultrasonic vibrating screen, with a combination of 400 and 800 mesh screens used to obtain finished material with a particle size distribution of 5-25 μm.

[0032] This embodiment systematically demonstrates a method for improving the performance of lithium iron phosphate cathode materials by dry ball milling composite multi-walled carbon nanotubes and graphene. Based on a lithium iron phosphate precursor with a specific particle size distribution, a mixed carbon nanomaterial system with controlled mass ratios is employed. An optimized ball milling process achieves initial material composite formation, followed by a staged pressure pre-forming treatment and a precisely temperature-controlled heat treatment regime, ultimately yielding a composite cathode material with an ideal particle size distribution. Characterization results show that this process successfully constructs a uniformly dispersed three-dimensional conductive network of carbon nanomaterials, enabling effective composite formation between carbon nanomaterials and the lithium iron phosphate matrix.

[0033] Example 2: Improving the energy density of lithium iron phosphate cathode materials through composite carbon nanomaterials In the raw material preparation stage, lithium iron phosphate precursor was prepared by co-precipitation: lithium hydroxide, iron oxide, and diammonium hydrogen phosphate were dissolved in deionized water in stoichiometric ratios, and the mixture was stirred and reacted in a 60°C water bath for 6 hours. The pH was adjusted to 7.5, and after centrifugation and washing, the precursor was vacuum dried at 80°C for 24 hours. The obtained precursor had an average particle size of 0.8 μm and a specific surface area of ​​15 m². 2 / g.

[0034] A composite system of multi-walled carbon nanotubes (MWCNTs) and reduced graphene oxide (RBO) at a mass ratio of 1:1 was selected. The MCCNTs were purified by acid washing: refluxed with 68% concentrated nitric acid at 85°C for 4 hours, then neutralized with 0.1 mol / L sodium hydroxide solution, and washed with deionized water until the conductivity was less than 5 μS / cm. The reduced graphene oxide was functionalized by nitrogen plasma treatment: treated at 100 W power and 50 Pa pressure for 30 minutes to introduce nitrogen-containing functional groups. X-ray photoelectron spectroscopy analysis showed that the nitrogen content in the treated material reached 3.5 at%.

[0035] A stepwise mixing process was employed for material composite formation. The first step involved wet mixing 60% of the pretreated carbon nanomaterials with a lithium iron phosphate precursor using N-methylpyrrolidone as the solvent. The solid content was controlled at 25%, and the mixture was dispersed at 400W ultrasonic power for 3 hours, maintaining the temperature below 20℃ during the ultrasonication process using an ice-water bath. After dispersion, the mixture was dried in an 80℃ vacuum drying oven for 12 hours, turning the material every 2 hours to ensure uniform drying. The dried mixture was then pressed into spherical preforms with a diameter of 2mm using a mold under a pressure of 30MPa. Rotary pressing technology was employed during pressing to ensure uniform preform density.

[0036] The heat treatment process is carried out in two stages. The first heat treatment is conducted under a nitrogen atmosphere: the temperature is increased from room temperature to 300℃ at a rate of 8℃ / min, then increased to 600℃ at a rate of 5℃ / min, and held at this temperature for 4 hours, followed by natural cooling to room temperature. This stage mainly completes the crystallization process of lithium iron phosphate and establishes a preliminary carbon-material interface bond. The second mixing involves adding the remaining 40% of the carbon nanomaterials and dispersing them using the same wet mixing parameters to ensure that the newly added carbon nanomaterials are fully dispersed in the formed composite matrix.

[0037] The second heat treatment was carried out in a tube furnace, using a mixture of argon and hydrogen (95:5 by volume) at a flow rate of 1.5 L / min. The temperature was raised to 450°C at a rate of 3°C / min and held for 2 hours to activate the carbon material; then, it was raised to 750°C at a rate of 2°C / min and held for 3 hours to complete the formation of the final composite structure. The cooling process employed programmed cooling: first, the temperature was lowered to 400°C at a rate of 5°C / min, then to 200°C at a rate of 2°C / min, and finally to room temperature at a rate of 1°C / min, taking approximately 15 hours in total. This slow cooling regime facilitated the release of internal stress and the stability of the crystal structure.

[0038] The post-processing steps include multi-stage crushing and precise classification. First, the lumpy material is coarsely crushed in a universal pulverizer, then finely crushed using a fluidized bed air classifier at a working pressure of 1.0 MPa. The classification process employs a combined screening system: first, larger particles are removed by a 200-mesh vibrating screen, then precise classification is achieved using a 400-mesh ultrasonic vibrating screen, and finally, an air classifier is used to obtain the final product with a particle size distribution of 2-15 μm.

[0039] This embodiment details a method for preparing lithium iron phosphate cathode materials based on stepwise composite and surface modification techniques. A combination of chemical pretreatment and plasma modification is used to functionalize carbon nanomaterials. Through a precisely designed two-step mixing and segmented heat treatment process, gradient composite and uniform distribution of carbon nanomaterials within the lithium iron phosphate matrix are achieved. The introduction of nitrogen-doped functional groups and the staged heat treatment regime effectively promote the bonding strength and structural stability of the material interfaces.

[0040] Finally, the following points should be noted: First, in the description of this application, it should be noted that, unless otherwise specified and limited, the terms "installation", "connection", and "linkage" should be interpreted broadly, and can be mechanical or electrical connections, or internal connections between two components, or direct connections. "Up", "down", "left", "right", etc. are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may change. Secondly: The accompanying drawings of the embodiments disclosed in this invention only involve the structures involved in the embodiments disclosed in this invention. Other structures can refer to the general design. In the absence of conflict, the same embodiment and different embodiments of this invention can be combined with each other. In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for improving the energy density of lithium iron phosphate cathode materials by using composite carbon nanomaterials, characterized in that, The method includes the following steps: S1: Provide a lithium iron phosphate cathode material precursor, wherein the precursor is prepared by mixing a lithium source compound, an iron source compound and a phosphorus source compound in a stoichiometric ratio, and wherein the average particle size of the precursor is in the range of 0.1 μm to 20 μm; S2: Provide carbon nanomaterials, said carbon nanomaterials being selected from carbon nanotubes, graphene, reduced graphene oxide, carbon nanofibers and combinations thereof, wherein the size of said carbon nanomaterials is in the range of 10 nm to 100 μm in length and 1 nm to 100 nm in diameter, and the amount of added carbon nanomaterials accounts for 0.5% to 15% of the total mass of the composite cathode material; S3: The carbon nanomaterials are uniformly mixed with the lithium iron phosphate cathode material precursor by dry mixing or wet mixing to form a mixture. The mixing intensity and time are controlled during the mixing process to ensure that the carbon nanomaterials are uniformly dispersed in the lithium iron phosphate. S4: The mixture is heat-treated under a protective atmosphere at a temperature between 500°C and 900°C for a time between 1 hour and 12 hours to form a composite structure between carbon nanomaterials and lithium iron phosphate, thereby obtaining a carbon nanomaterial composite lithium iron phosphate cathode material. S5: Cooling and optional post-processing steps are performed on the composite cathode material. The cooling adopts a controllable cooling method with a cooling rate in the range of 1℃ / min to 10℃ / min. The post-processing includes grinding and sieving to obtain the target particle size distribution.

2. The method for improving the energy density of lithium iron phosphate cathode material by using composite carbon nanomaterials according to claim 1, characterized in that, In S2, the carbon nanomaterial is a mixture of multi-walled carbon nanotubes and graphene, wherein the mass ratio of multi-walled carbon nanotubes to graphene is between 1:0.2 and 1:5, and in S3, the mixing is achieved by mechanical stirring or ultrasonic-assisted dispersion, and the mixing time is between 1 h and 10 h.

3. The method for improving the energy density of lithium iron phosphate cathode material by using composite carbon nanomaterials according to claim 1, characterized in that, In S3, the dry mixing is carried out using a ball mill, with a ball milling speed between 100 r / min and 500 r / min and a ball milling time between 3 h and 15 h; the wet mixing is carried out using a solvent dispersion method, with the solvent including water or organic solvent, and ultrasonic energy is applied during the dispersion process, with an ultrasonic power between 100 W and 1000 W and a dispersion time between 30 min and 5 h.

4. The method for improving the energy density of lithium iron phosphate cathode material by using composite carbon nanomaterials according to claim 1, characterized in that, In S4, the heat treatment step is carried out in an inert atmosphere, which includes nitrogen or argon, with the gas flow rate controlled between 0.5 L / min and 5 L / min. The heat treatment process includes heating to the target temperature at a heating rate of 2 °C / min to 10 °C / min and holding at that temperature for a certain period of time, which is in the range of 2 h to 8 h.

5. The method for improving the energy density of lithium iron phosphate cathode material by using composite carbon nanomaterials according to claim 1, characterized in that, The method further includes preforming the mixture before S4 by forming a blank through tableting or granulation to enhance the physical contact between the carbon nanomaterials and lithium iron phosphate, with the preforming pressure ranging from 10 MPa to 100 MPa.

6. A method for improving the energy density of lithium iron phosphate cathode material by using composite carbon nanomaterials according to claim 1, characterized in that, In S2, the carbon nanomaterial undergoes a pretreatment step before composite processing. The pretreatment includes acid washing purification or surface functionalization modification. The acid washing is performed by refluxing concentrated nitric acid or concentrated sulfuric acid at a temperature of 60°C to 100°C for 1 to 6 hours. The surface functionalization modification is achieved by chemical grafting or plasma treatment.

7. A method for improving the energy density of lithium iron phosphate cathode material by using composite carbon nanomaterials according to claim 1, characterized in that, In S5, the post-processing step includes air jet milling or vibratory sieving of the composite cathode material to obtain a final product with a particle size distribution between 1 μm and 50 μm.

8. A method for improving the energy density of lithium iron phosphate cathode material by using composite carbon nanomaterials according to claim 1, characterized in that, The method also includes a material characterization step after S5, in which the uniformity of the composite structure is examined by X-ray diffraction or scanning electron microscopy.

9. A method for improving the energy density of lithium iron phosphate cathode material by using composite carbon nanomaterials according to claim 1, characterized in that, In S2, the carbon nanomaterials include functionalized carbon nanomaterials. The functionalization is achieved by introducing oxygen- or nitrogen-containing functional groups. In S3, a stepwise mixing method is adopted, in which a portion of the carbon nanomaterials are first mixed with the lithium iron phosphate precursor, then heat treatment is performed in S4, and then the remaining carbon nanomaterials are added for secondary mixing.

10. A method for improving the energy density of lithium iron phosphate cathode material by using composite carbon nanomaterials according to claim 1, characterized in that, In S3, the mixing process further includes adding a dispersant to promote uniform dispersion of the carbon nanomaterials. The amount of the dispersant is 0.1% to 5% of the total mass of the mixture, and the dispersant is selected from surfactants or polymeric dispersants.